Pendidikan Islam Multikultural: Perspektif Filsafat untuk Membangun Generasi Toleran - Fita Salsabella, Alzahra; Mutia Agustina, Ira; Puspika Sari, Herlini (Al-Mau'izhoh: Jurnal Pendidikan Agama Islam, 2025)
This study examines multicultural Islamic education from a philosophical perspective as an effort to build a tolerant generation in a pluralistic society. Indonesia, as a multicultural nation, faces challenges such as rising intolerance and radicalism, reflecting a gap between the values of Islam rahmatan lil ‘alamin and social reality. Using a qualitative approach through library research, this study explores the integration of tauhid (divine unity), justice (‘adl), and humanism in Islamic education. The findings show that multicultural Islamic education is founded on tauhid as the basis of human unity, justice as a moral pillar, and humanism as respect for human dignity. The integration of these values creates an educational paradigm that balances cognitive development with character formation and social awareness. Philosophy plays a key role in fostering critical, reflective, and open-minded thinking to promote inclusive and equitable education. Multicultural Islamic education thus serves as a strategic means of shaping a moderate, tolerant, and virtuous generation. The application of multicultural values through curriculum design, learning methods, and teachers’ exemplary roles is essential to achieving social harmony within Indonesia’s diversity.